Vertical Profiles and Chemical Properties of Aerosol Particles upon Ny-Ålesund (Svalbard Islands). (29th June 2015) - Moroni, B.; Becagli, S.; Bolzacchini, E.; Busetto, M.; Cappelletti, D.; Crocchianti, S.; Ferrero, L.; Frosini, D.; Lanconelli, C.; Lupi, A.; Maturilli, M.; Mazzola, M.; et al.
Abstract : Size-segregated particle samples were collected in the Arctic (Ny-Ålesund, Svalbard) in April 2011 both at ground level and in the free atmosphere exploiting a tethered balloon equipped also with an optical particle counter (OPC) and meteorological sensors. Individual particle properties were investigated by scanning electron microscopy coupled with energy dispersive microanalysis (SEM-EDS). Results of the SEM-EDS were integrated with particle size and optical measurements of the aerosols properties at ground level and along the vertical profiles. Detailed analysis of two case studies reveals significant differences in composition despite the similar structure (layering) and the comparable texture (grain size distribution) of particles in the air column. Differences in the mineral chemistry of samples point at both local (plutonic/metamorphic complexes in Svalbard) and remote (basic/ultrabasic magmatic complexes in Greenland and/or Iceland) geological source regions for dust. Differences in the particle size and shape are put into relationship with the mechanism of particle formation, that is, primary (well sorted, small) or secondary (idiomorphic, fine to coarse grained) origin for chloride and sulfate crystals and transport/settling for soil (silicate, carbonate and metal oxide) particles. The influence of size, shape, and mixing state of particles on ice nucleation and radiative properties is also discussed.